Analysis Of Thematic Exam Questions for Fifth Grade Elementary School Students, Theme VI, Even Semester In Sibolga City - Tiflah Addina Khairiah Nasution; Sumarno; Ajat Sudrajat (Jurnal Perspektif, 2026)
The purpose of this study was to determine the quality of the exam questions tested on students in the even semester of grade 5 of elementary school. This study is a qualitative study. The data collection in the form of exam questions and student answer keys will be examined using Anates ver.0.9 media technology to determine the level of quality of the tests tested on students. The results of this study prove that there is a sufficient level of conformity between the question grids that have been provided with the questions that have been evaluated. When viewed from the characteristics of the questions based on Bloom's Taxonomy in the even semester exam questions, both thematic and topic questions, many questions use low characteristics, in fact not a single question was found that fell into the high characteristic category. There is a contrast or difference in effectiveness between exam questions that use thematic and exams that use subjects. The number of valid questions related to thematic test topics in SD Negeri 081234 and SD Negeri 084081 is fewer than the number of questions related to subjects in SD Negeri 084087 and SD Negeri 081224. Reliability scores are higher for level assessments, as well as for questions that focus more on themes than specific subjects. The level of difficulty of the questions is determined by the number of questions other than subject matter that are included in the difficult category.